(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
In this article, the establishment of a socially oriented market economy in Uzbekistan. One of the main goals of the development is small business and private entrepreneurship in the country from the priority development of forms, economic to realize this goal carrying out reforms, creating large-scale institutional bases for increasing its role, organization of business activity and legal and regulatory documents guaranteeing it, organization of activities of non-governmental organizations and enterprises assisting entrepreneurs has been studied.